An Alternative Route for Entrapped Inferior Orbital Nerve in Orbital Floor Fracture. Issue 3 (September 2017) - Rao, Anantheswar Y. N.; Jesudas, Joyce
Orbital floor fractures pose a grave threat for injury to the infraorbital nerve, resulting in the patient suffering from a disturbing paraesthesia. It is challenging for the operating surgeon to release and secure the entrapped nerve with reconstruction of the orbital floor. We present an interesting case of orbital floor fracture with entrapped infraorbital nerve, wherein we have decompressed the nerve and provided it, a new course.